2011
DOI: 10.1111/j.1439-0531.2011.01917.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Embryo Production in Llamas (Lama glama) from In vivo Matured Oocytes with Raw Semen Processed with Androcoll‐E using Defined Embryo Culture Media

Abstract: The aim of this study was to carry out in vitro fertilization using spermatozoa selected with Androcoll-E™ and to evaluate the efficiency of the culture medium DMEM-F12 for in vitro embryo development in the llama. Twelve adult females from 18 superstimulated (67%) were used as oocyte donors. They were superstimulated with 1500 IU of eCG and after 5 days, received a single dose of buserelin. Twenty hours post-injection, follicular aspiration was conducted by flank laparotomy. Semen collections were performed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 25 publications
3
21
0
6
Order By: Relevance
“…In another species of camel (Lama glama), IVP attained 17% at blastocysts stage (Conde et al 2008). Trasorras et al (2012) found a lower rate of blastocysts reaching 9%.Recently, blastocyst rate ranged between 34-36% using TALP culture medium in the same living species (Trasorras et al 2014). As a result of this, cleavage rate of camel oocytes varies according to the type of culture medium (Khatir et al 2005), the size of follicle (Khatir et al 2007) and co-culture with granulosa or oviductal cells (Khatir et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In another species of camel (Lama glama), IVP attained 17% at blastocysts stage (Conde et al 2008). Trasorras et al (2012) found a lower rate of blastocysts reaching 9%.Recently, blastocyst rate ranged between 34-36% using TALP culture medium in the same living species (Trasorras et al 2014). As a result of this, cleavage rate of camel oocytes varies according to the type of culture medium (Khatir et al 2005), the size of follicle (Khatir et al 2007) and co-culture with granulosa or oviductal cells (Khatir et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Trasorras et al. () found increased percentages of positive HOST when using SLC for selecting fresh llama sperm.…”
Section: Discussionmentioning
confidence: 87%
“…Recent research indicates that SLC‐selected sperm also produce less hydrogen peroxide than controls (Morrell, Lagerqvist, Humblot, & Johannisson, ). Enhanced fertility characteristics have been reported for SLC sperm, and their fertility confirmed for some species (stallion, Morrell, Richter et al., ; bull, Thys et al., ; boar, Sjunnesson, Morrell, & González, ; and llama, Trasorras et al., ) despite the removal of seminal plasma proteins and possibly cholesterol during processing (Kruse, Dutta, & Morrell, ).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations